Effect of Ruellia Praetermissa Extracts on Erythropoiesis in Pregnant Women - Martin, Salah A; Anna, Njunda L (Bangladesh Journal of Physiology and Pharmacology, 2014)
The effect of the extracts of Ruellia Praetermissa on hemoglobin (Hb), Hematocrit (Ht), mean corpuscular hemoglobin (MCH), mean corpuscular volume (MCV). mean corpuscular hemoglobin concentration (MCHC), red blood cell count (RBC), was investigated in 50 Pregnant women attending prenatal clinic in Belo maternity. The women were assigned to 5 groups of 10 women per group. The first group was the control and the other 4 were the experimental groups. The control was administered daily, 0.5 ml of saline solution while the experimental groups were administered daily oral doses of the plant extract in concentrations of 200mg/kg, 400mg/kg, 800mg/kg and 1,600mg/kg respectively for 16 days. Blood samples were collected on the 17th day and analyzed. The extracts contain flavonoids aglycons (luteolin and apigenin) and their respective, glycosides and a high concentration of triterpens (campesterol, stigmasterol, -sitosterol, lupeol) and iridoid glycosides. It is also rich in vitamins and minerals. The extracts increased the values in a dose dependent manner Hb (P < 0.05), RBC (P < 0.05), hematocrit (P < 0.05). It however showed no remarkable effect on the values of MCH and MCHC (P > 0.05) but with a dose depending decreasing effect on MCV (P < 0.05). The active principles of this plant drug stimulate erythropoiesis which leads to increase in circulating RBCs with slightly microcytic sizes (MCV), normochromic weight,(MCH) normochromic hemoglobin contents (MCHC). The result of this study thus supports the traditional use of Ruellia Praetermissa in pregnancies threatened with miscarriage and as a remedy for anemia. DOI: http://dx.doi.org/10.3329/bjpp.v28i1-2.20075 Bangladesh J Physiol Pharmacol 2012; 28(1&2):15-18